2006
DOI: 10.1002/joc.1324
|View full text |Cite
|
Sign up to set email alerts
|

East Asian dust storm and weather disturbance: possible links to the Arctic Oscillation

Abstract: In this work, the authors investigated the spring dust storm frequency variations in northern China and its relationship with weather disturbances, cold high, eddy kinetic energy (EKE), as well as the impact of the Arctic Oscillation (AO) on the dust storm frequency variations. It is found that there is a significantly decreasing trend of −26%/10 years in the dust storm frequency variations. In addition, the year-to-year variations are also remarkable, which account for 58.3% of the total variance of the dust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 54 publications
3
64
0
Order By: Relevance
“…During the winter season, the AO signal is reflected in fields like surface temperature in the northern hemisphere (Thompson & Wallace 2001), precipitation in China (Gong & Wang 2003), sea ice over north polar and sub-polar regions (Wang & Ikeda 2000), and lower tropospheric circulations including the East Asian winter monsoon, Aleutian low, and Siberian high (Gong et al 2001, Wu & Wang 2002. During the spring season, the AO is closely related to dust storm frequency in northeast Asia (Gong et al 2006, Mao et al 2011a, Mao et al 2011b, and even has a lag effect on the following summer monsoon rainfall in East Asia (Gong & Ho 2003, Gong et al 2011). The majority of previous studies have emphasized the AO's effect on seasonal mean climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the winter season, the AO signal is reflected in fields like surface temperature in the northern hemisphere (Thompson & Wallace 2001), precipitation in China (Gong & Wang 2003), sea ice over north polar and sub-polar regions (Wang & Ikeda 2000), and lower tropospheric circulations including the East Asian winter monsoon, Aleutian low, and Siberian high (Gong et al 2001, Wu & Wang 2002. During the spring season, the AO is closely related to dust storm frequency in northeast Asia (Gong et al 2006, Mao et al 2011a, Mao et al 2011b, and even has a lag effect on the following summer monsoon rainfall in East Asia (Gong & Ho 2003, Gong et al 2011). The majority of previous studies have emphasized the AO's effect on seasonal mean climate.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies have emphasized the AO's effect on seasonal mean climate. A few studies have analyzed possible linkages between AO and extreme weather/climate events, including cold air activity and blocking activity throughout the hemisphere (Thompson & Wallace 2001), synoptic temperature variance over East Asia (Gong et al 2004), extreme temperatures in the northeastern United States and Canada (Wettstein & Mearns 2002), and synoptic scale disturbances in East Asia (Gong et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Ikeda, 2000;Bamzai, 2003;Gong et al, 2007), East Asian dust events (e.g. Kang and Wang, 2005;Gong et al, 2006), and the Asian monsoon system (e.g. Gong et al, 2001;Wu and Wang, 2002;Gong and Ho, 2003;Ju et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During the period 1954-1998, the spring dust storms in North China have been found to be closely associated with changes in the atmospheric circulation patterns which are influenced by global ice-snow cover, and it is also noted out that the Arctic ice-snow cover can be used for the decadal prediction of dust storm activities . The impacts of the Arctic and Antarctic Oscillations on dust storms are analysed in the studies of Gong et al (2006) and Fan and Wang (2004), respectively. It has been identified that there is a close relationship between the Arctic Oscillation and the interannual variation of dust storm frequency in northern China (Gong et al, 2006), and the yearly variations of the Antarctic Oscillation have also been found to play a significant role in the dust-related atmospheric circulation during boreal springs in China.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of the Arctic and Antarctic Oscillations on dust storms are analysed in the studies of Gong et al (2006) and Fan and Wang (2004), respectively. It has been identified that there is a close relationship between the Arctic Oscillation and the interannual variation of dust storm frequency in northern China (Gong et al, 2006), and the yearly variations of the Antarctic Oscillation have also been found to play a significant role in the dust-related atmospheric circulation during boreal springs in China. Two possible mechanisms are recognized for the coupling of the Antarctic Oscillation and the frequency of dust-forming weather, one of which is related to a meridional circulation pattern and the other Figure 1.…”
Section: Introductionmentioning
confidence: 99%